How the Ends of Bones Evolve and What They Do: The Anatomical and Biomechanical Perspective - Putz, Reinhard; Boszczyk, Bronek; Milz, Stefan (Seminars in Musculoskeletal Radiology, 2019)
Skeletal ossification occurs either directly within mesenchymal tissues or indirectly through a template of hyaline cartilage. Between the epiphyses and diaphyses of long bones, hyaline cartilaginous growth plates remain and constitute the progenitor cell reservoir from which the tissue develops toward the diaphysis and determines longitudinal bone size. Growth plates exhibit a characteristic architecture with columnar cell organization and different zonal morphology. The cells increase their volume toward the diaphysis, and eventually the longitudinally arranged septa of extracellular matrix mineralize. Finally, the mineralized cartilage matrix is replaced by lamellar bone. The extracellular matrix is rich in glycosaminoglycans, proteoglycans, and collagen II; at the edges of the growth plates, collagen I, III, and collagen X, especially at the mineralization front, are also present.The geometry of the growth plates is regulated by the local mechanical environment. In general, all plates orient themselves perpendicular to the resulting compressive force vector; grooves, ridges, and lateral angulations are adaptations to withstand shear forces acting on the growth plates. The final shape of the fully grown bone is determined not only by the epiphyseal growth plates but also by their apophyseal counterpart. Both structures respond in a comparable fashion to the local mechanical environment.
Keywords: bone ends; epiphysis; apophysis; epiphyseal plate; growth plate